2014
DOI: 10.1017/s095457941400011x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with borderline personality and their young children: Adult Attachment Interviews, mother–child interactions, and children's narrative representations

Abstract: Borderline personality disorder (BPD) involves disruptions in attachment, self, and self-regulation, domains conceptually similar to developmental tasks of early childhood. Because offspring of mothers with BPD are at elevated risk of developing BPD themselves (White, Gunderson, Zanarini, & Hudson, 2003), studying them may inform precursors to BPD. We sampled 31 children age 4-7 whose mothers have BPD and 31 normative comparisons. We examined relationships between mothers' Adult Attachment Interview (AAI) repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 79 publications
5
37
1
Order By: Relevance
“…Similarly, Whipple, Bernier, and Mageau (2011) found that Preoccupied states of mind were associated with a more intrusive style compared to Dismissing states of mind. It is similarly consistent with recent research examining the latent structure of the AAI that has highlighted, using principal component analysis, two dimensions that separate preoccupied/unresolved and dismissing features of AAI narratives (Macfie, Swan, Fitzpatrick, Watkins, & Rivas, 2014;Roisman et al, 2007;Whipple et al, 2011). This highlights the qualitative differences in emotion mind-mindedness between Preoccupied and Dismissing attachment patterns and the importance of using attachment measures that allow these differences to be elucidated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Whipple, Bernier, and Mageau (2011) found that Preoccupied states of mind were associated with a more intrusive style compared to Dismissing states of mind. It is similarly consistent with recent research examining the latent structure of the AAI that has highlighted, using principal component analysis, two dimensions that separate preoccupied/unresolved and dismissing features of AAI narratives (Macfie, Swan, Fitzpatrick, Watkins, & Rivas, 2014;Roisman et al, 2007;Whipple et al, 2011). This highlights the qualitative differences in emotion mind-mindedness between Preoccupied and Dismissing attachment patterns and the importance of using attachment measures that allow these differences to be elucidated.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the similarity in mind-mindedness between Preoccupied and Unresolved could be reflective of the high number of mothers with secondary classifications of Preoccupied in the Unresolved sample (67%). However, recent research on the latent structure of the AAI using principal component analysis has also revealed that Preoccupied and Unresolved narrative qualities on the AAI tend to cluster to form a single dimension, with a second dimension encompassing dismissive narrative features (Macfie et al, 2014;Roisman et al, 2007;Whipple et al, 2011). As such, it is possible that the emotional communication style of mothers with Preoccupied and Unresolved attachments may share some common features.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, factor analytic techniques have been used to identify the number of latent factors that underlie covariation among the AAI attachment state of mind ratings and the degree to which specific rating scales load on the various latent variables (see Haltigan, Roisman, & Haydon, 2014, for an overview of research on the factor structure of the AAI). The factor analytic results from over 10 separate samples have provided robust evidence that the variation in the AAI ratings of individuals’ attachment states of mind is accounted for by two latent variables: one reflecting individuals’ dismissing states of mind and the other reflecting individuals’ preoccupied states of mind (Bernier, Larose, Boivin, & Soucy, 2004; Haltigan, Leerkes, Supple, & Calkins, 2014; Haltigan, Roisman, et al, 2014; Larose & Bernier, 2001; Macfie, Swan, Fitzpatrick, Watkins, & Rivas, 2014; Martin et al, 2017 [this issue]; Raby, Labella, Martin, Carlson, & Roisman, 2017 [this issue]; Roisman et al, 2007; Scharf, Mayseless, & Kivenson-Baron, 2012; Whipple, Bernier, & Mageau, 2011). …”
Section: Latent Structure Of Adults’ Attachment States Of Mindsmentioning
confidence: 99%
“…Another study [29] found that a history of childhood trauma and particularly emotional and sexual abuse was higher for those adults with social anxiety compared to psychiatric and healthy controls. Kaehler and Freyd [16] examined physical abuse history and found that this kind of significant relationship betrayal predicted BPD features in women, and mothers with diagnosed BPD were more likely to have preoccupied/unresolved attachment status but not more likely to be dismissive [30]. In a study of people presenting at a psychiatric outpatient clinic [31], physical and emotional child abuse history was positively correlated with elevated scores on the MMPI-2 in a number of different dimensions including psychopathic deviate, paranoia, psychasthenia, and schizophrenia.…”
Section: Attachment Relationship Trauma and Abusementioning
confidence: 99%